the reality of Secondary students use of social media spaces such as Instagram and TIK TOK its most important repercussions on their family upbringing: a field study on some students studying in the secondary stage - leyla, ouanas; Guendouz, monir (Journal of Social Sciences and Humanities, 2025)
Social media or virtual spaces are now and in all societies is known as the new social information, which is witnessing a dynamic movement of development and spread that has a clear and visible impact on socialization in general and on family upbringing in particular The latter usually appears in the exterior appearance of the children or in the character of the children, Because new generations have become totally dependent on these virtual spaces at all stages of life or even daily life after the first goal of using these virtual sites was primarily learning in this particular age group. And because tracers of prevailing social conditions are aware that the use of these virtual spaces has taken a special direction as it moves towards affecting social construction in general and families in particular And so our study came to stop the reality of the use of these virtual spaces, especially the use of Instagram and TikTok in high school children and the most important implications for their family upbringing, In this study, we rely more on the field side for more realistic results. In this field study, we focus on some secondary students and their use of Instagram and TikTok in the city of Mesaila.